Perceptions of trust in bionano sensors: Is it against our better judgement? An investigation of generalised expectancies and the emerging technology trust paradox - Natasha CHL Mazey; Stephen C Wingreen (International Journal of Distributed Sensor Networks)
This article examines the literature surrounding bionano sensors, its anticipated applications and biological risks associated with their use. Despite being largely unfamiliar with bionano technology, existing research indicates that individuals are optimistic about bionano technologies and are seemingly nonchalant about their potential risks. This would suggest individuals may hold significant positive trust beliefs in bionano sensors, contrary to the predictions of technology trust theory. This article draws on McKnight et al.’s technology trust model and generalised expectancies of technology (perceived functionality, reliability and effectiveness). Using experimental procedure, this article confirms that individuals perceive bionano sensors to be a trustworthy technology and seeks to understand this ‘emerging technology trust paradox’.